ИНТЕРАКТИВНЫЕ МЕТОДЫ ОБУЧЕНИЯ РУССКОМУ ЯЗЫКУ СТУДЕНТОВ ИНСТИТУТА СОРБОННА-КАЗАХСТАН («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article is devoted to interactive methods of teaching Russian language to students of the Sorbonne-Kazakhstan Institute at the Kazakh National Pedagogical University named after Abay. Interactive learning methods allow to intensify the process of understanding, learning, creative application of knowledge in the solution of practical tasks.
Keywords: communicative method, active method, interactive method, case-method, quiz.